2002
DOI: 10.1007/s00436-001-0556-5
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial 12S gene is a suitable marker of populations of Sarcoptes scabiei from wombats, dogs and humans in Australia

Abstract: We sequenced part of the mitochondrial 12S ribosomal RNA gene of 23 specimens of Sarcoptes scabiei from eight wombats, one dog and three humans. Twelve of the 326 nucleotide positions varied among these mites and there were nine haplotypes (sequences) that differed by 1-8 nucleotides. Phylogenetic analyses indicated that these mites were from two lineages: (1) mites from wombats from Victoria, Australia, and mites from the humans and dog from the Northern Territory, Australia (haplotypes 1-4, 9); and (2) mites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 17 publications
0
52
0
Order By: Relevance
“…Previous molecular studies of S. scabiei in animals and humans have utilized various gene targets, such as microsatellites, ITS-2 ribosomal DNA (rDNA), mitochondrial 12S/16S rRNA, and S. scabiei myosin heavy chain genes (41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Previous molecular studies of S. scabiei in animals and humans have utilized various gene targets, such as microsatellites, ITS-2 ribosomal DNA (rDNA), mitochondrial 12S/16S rRNA, and S. scabiei myosin heavy chain genes (41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…As a heuristic test of this second idea, we analysed the mitochondrial rrnS data of Skerrat et al (2002) for the ectoparasitic mite Sarcoptes scabiei (Acari) in Australia, …”
Section: Other Factors Affecting Population Expansionsmentioning
confidence: 99%
“…One of these universal primer sequence sets is included within a region of the 12S rRNA. This region has been highly informative in the examination of phylogenetic relationships [25][26][27][28][29]. In this study, dust mite 12S rRNA mtDNA sequences are reported for the first time and used to establish evolutionary relationships between the four domestic mite families Pyroglyphidae, Glycyphagoidea, Acaridae, and Echimyopodidae represented by Dp, Glycyphagus privatus (Gp), Aleuroglyphus ovatus (Ao), and Blomia tropicalis (Bt), respectively.…”
Section: Introductionmentioning
confidence: 99%